2016
DOI: 10.1039/c5cp02305j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nitrogen species incorporated into graphite using low energy nitrogen ion sputtering

Abstract: The electronic structures of nitrogen species incorporated into highly oriented pyrolytic graphite (HOPG), prepared by low energy (200 eV) nitrogen ion sputtering and subsequent annealing at 1000 K, were investigated by X-ray photoelectron spectroscopy (XPS), angle-dependent X-ray absorption spectroscopy (XAS), and Raman spectroscopy. An additional peak was observed at higher binding energy of 401.9 eV than 400.9 eV for graphitic1 N (graphitic N in the basal plane) in N 1s XPS, where graphitic2 N (graphitic N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Both center N and valley N are graphitic N connected to three carbon atoms, existing in the graphite basal plane, and at graphite zigzag edges or vacancy sites, respectively [ 18 , 19 ]. The detailed peak assignment of each component was discussed in our previous report [ 12 ]. The estimated amount of each nitrogen component from the fitting results is summarized in Table 1 ; center N is the most prevalent, followed by valley N and pyridinic N.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both center N and valley N are graphitic N connected to three carbon atoms, existing in the graphite basal plane, and at graphite zigzag edges or vacancy sites, respectively [ 18 , 19 ]. The detailed peak assignment of each component was discussed in our previous report [ 12 ]. The estimated amount of each nitrogen component from the fitting results is summarized in Table 1 ; center N is the most prevalent, followed by valley N and pyridinic N.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The spectra are normalized according to the intensity at 430 eV. Three sharp peaks in the π* region can be assigned to pyridinic N (A), cyanide N (B), and graphitic N (center N and valley N) (C) [ 12 , 30 ]. A peak at 407.5 eV corresponds to the σ* state of the nitrogen components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The matter is further complicated by the fact that the relative merits of the different functionalities are still not fully understood. [6][7][8][9][10]23,[46][47][48][49] However, clearly nitrogen doping is not enough -the nitrogen atoms also need to be exposed to solution, if their presence is to be felt. Thus, the most important microstructural parameter may be specific surface area -also closely correlated with micropore volume -which determines the solution exposure of active sites.…”
Section: Resultsmentioning
confidence: 99%
“…Graphitic-N can be found either in-plane or along the edge. Kiuchi et al reported on the nitrogen doping of pyrolytic graphite prepared by low energy nitrogen ion sputtering and subsequent annealing at less than 800 °C [40]. As the nitrogen concentration decreased, two graphitic nitrogen components were identified: a graphitic-N in the basal plane (nitrogen bonded to three carbon atoms) at 400.9 eV, and a graphitic-N in the zigzag edge and/or vacancy sites with a binding energies of 401.9 eV.…”
Section: Changes In Carbon Fiber Propertiesmentioning
confidence: 99%